Design Optimization of the Bolted Connection Loaded Parallel to the Timber Grain for Masonry Building Retrofits - Abdul Razak, Abdul Karim; Pierre, Quenneville; Norazzlina, M.Sa'don (NAUN Publication, 2022)
The experimental results of timber bolted connection tests for the purpose of optimizing the use of current design standard are presented. The test was conducted to investigate the structural performance of bolted connections loaded parallel to the timber grain. Both ductile and brittle failure modes were investigated to identify the governing parameters that affect the types of failures. The Meraka hardwood was chosen because it was found to be commonly used in the construction of the structural components of floor and roof diaphragms in Malaysia unreinforced masonry (URM) buildings. From this study, a wood database can be established for assisting the design engineers in developing the retrofitting technique of the building, especially the timber diaphragm joint part of the wall-diaphragm connections. Eighteen characteristics of steel-wood-steel (SWS) with a single row bolted joints were tested in tension, whereas ten specimens were prepared for each connection group. From the results obtained, it can be observed that the current timber design code is far too conservative compared to the optimized design proposed in this paper.